Direct quenching and tempering to achieve high strength and toughness of GPa-Grade nano-precipitated steel: The effect of precipitation behavior and variant selectivity - Zhongde Pan; Enmao Wang; Huibin Wu; Junping Wu; Jun Hong; Zhongzhu Liu; Aimin Guo; Zhen Sun; Yansen Hao (Journal of Materials Research and Technology)
In order to satisfy the application requirements for strength and toughness of hydropower steels for large pumped storage power plants. In this study, based on the synergy of deformation and phase transition, the trade-off between strength and toughness was broken, and the GPa-grade nano-precipitated steel was prepared by direct quenching and tempering. The effects of Nb–V–Ti composite nano-precipitation behavior and martensite variant selectivity on the strengthening and toughening mechanisms were highlighted. The results show that directly quenched steel has the optimal comprehensive mechanical properties after tempering at 550 °C. Combining the contributions of various strengthening mechanisms, the increase in the yield strength relative to off-line quenching and tempering is mainly attributed to additional dislocation strengthening (∼33 MPa) and precipitation strengthening (∼174 MPa). Direct quenching enhances the homogeneous nucleation of finer mono- and binary precipitates and their stable growth during tempering, while the ternary precipitates do not suffer from elemental inhomogeneities due to lack of re-dissolution. Furthermore, the high-frequency variants of the dominant close-packed plane group tend to form high-angle grain boundaries with different orientations and planar alignments, derived from the refinement of Bain groups induced by the self-plasticity modulation of martensite transition due to the accumulation of deformed geometrically necessary dislocations and finite dislocation slip.